Research of development of corporate culture of modern industrial enterprise - Karpenko, Andriy; Kolyada, Yulia (Management and Entrepreneurship: Trends of Development, 2017)
Purpose. The purpose is theoretical study of aspects of corporate culture in the enterprise, in the context of factors influencing its formation and development, development of methodological and practical recommendations for improvement of the mechanism of corporate culture.Design/methodology/approach. The theoretical and methodological basis of the study was the work of domestic and foreign scientists, who devoted to the study of the mechanism of influence of corporate culture on the activities of enterprises, system and process approaches, functional-target and abstract-logical methods has been used.Findings. The subject of the study is the relations that arise in the development of corporate culture. The urgency of the topic is that the problem of the impact of corporate culture on the internal environment of enterprises was previously underestimated and at the moment requires special attention from the side of managers to create an effective mechanism of internal corporate governance, since staff is the main resource of any enterprise and it is on the development and improvement of conditions for Its better functioning is directed by most managerial tools.Research limitations/implications. The scientific significance is to analyze the process of developing the corporate culture of an industrial enterprise and its impact on the work of employees in modern conditions.Originality/value. As a conclusion, suggestions are made to improve the mechanism of corporate culture, depending on the needs of the personnel of the enterprise. In practice, this will improve the socio-cultural process and image of the enterprise in the eyes of the workers